Comprehensive numerical model for the analysis of potential heat recovery solutions in a ceramic industry. (May 2021) - Venturelli, M.; Brough, D; Milani, M.; Montorsi, L.; Jouhara, Hussam
Highlights: 0D-1D numerical approach for the energy efficiency in process industry. A TRNSYS crossflow HPHE model has been developed to simulate transient behaviour. Heat recovery from ceramic kiln exhaust to preheat combustion air in spray dryer. Simulation of the dynamic behaviour of the entire heat recovery system. Analysis of the thermal management strategy to highlight critical conditions. 3D maps of the main operating parameters to support the real control system design. Abstract: Heat recovery opportunities and total plant energy efficiency improvements need to be evaluated before manufacturing the real components when addressing the energy and economic effectiveness in industrial applications. Numerical modelling of the complete energy systems can be a key design tool in order to investigate the potential solutions to improve the performance of the considered system. In this study, a 0D/1D numerical analysis and transient system simulation analysis are adopted to investigate the energy efficiency enhancement given by the application of a heat pipe-based heat exchanger in the ceramic industry. The thermal power is recovered from the exhaust gases of the kilns used to fire the tiles. The numerical model includes all the main components of the heat recovery system: the primary side of the exhaust gases, the heat exchanger, the secondary circuit of the heat transfer fluid and the heat sink where the thermal power is exploited. Particular care is devoted to the modelling of the heat pipe-based heat exchanger and the necessary control strategy of the system; a specific model for the simulation of the secondary side pump is also accounted for in the analysis. The numerical results of the primary circuit are validated against experimental measurements carried out on the real ceramic facility. The good agreement between the numerical and experimental results demonstrates that the numerical model is an appropriate tool for investigating the energy efficiency enhancement of an industrial plant and for evaluating different configurations and solutions in order to fulfil the industry requirements.